Analisis Anak Berkebutuhan Khusus Ketunaan ADHD di SDN Petir 2 Kota Tangerang - Nurfadhillah, Septy; Prabandani, Riana Okta; Rini, Emilia Septia; Putri, Amelia Agdira; Handayani, Susi Susanti; Asshiddiq, Akmal; Awaliyah, Sapitri (YASIN, 2021)
The purpose of this study was to find out how the implementation of inclusive education services, especially ABK with ADHD at SDN PETIR 2 Tangerang City. The type of research that the researcher finally chose was qualitative research. During the data collection process, it was carried out in several ways, namely observation, interviews, and documentation in the form of photos and sound recordings. Then the analysis technique goes through several stages, namely selection, simplification, classification, concentration, linking, and drawing conclusions. The results of the interview revealed that SDN PETIR 2 KOTA TANGERANG implements inclusive education with the same curriculum and evaluation as other students, only slightly simplified. This makes students with special needs get the same education but according to their abilities.